Ansiedade da hospitalização em Crianças: análise conceitual - Souza, Gabriela Lisieux Lima de (2014)
Introduction: The child's hospitalization is characterized by an extremely stressful which could lead to negative consequences in their development, such as the anxiety of hospitalization in children. Objective: To analyze the concept of anxiety of hospitalization in children, identifying their attributes, antecedents and consequences, with a view to building a nursing diagnosis. Method: It was taken based on the model conceptual analysis proposed by Walker and Avant, which aims to clarify the meanings of terms, being composed of eight stages: concept selection, choice of targets, aims and objectives of conceptual analysis, identification of possible uses of the concept, determining critical attributes, defining or essential, construction of model cases, development of other cases, identification of antecedents and consequences of the concept and definition of empirical referents. The data collection was made possible through close reading of the literary corpus consists of 46 papers that focused on the theme, published in the languages Portuguese, English and Spanish in the period 2006-2013. For its operation, we proceeded with the extraction of the phenomena that were related to the attributes, antecedents and consequences of the concept under study. Results: As a result, it was possible to identify the attributes, classified as biological needs (changes in appetite, dyspnea and respiratory sensation of constriction, sympathetic stimulation, arousal and tachycardia, insomnia and Increased alertness, and psychological needs (apprehension, wow, conflict, restlessness of mind, lack of concentration and inattention, hyperactivity, impulsivity, agitation and restlessness, irritability and anger, fear, dread and anxiety, nervousness, loss of self-confidence, insecurity, impotence and loss of autonomy, concern, sense of abandonment, loneliness and helplessness, feeling guilt and punishment, injury or assault, stress, tremors and sadness) for the background, we selected the clearance in the familiar context, lack of procedures, experiences submission to invasive procedures, hospitalizations previous/ experience of pain/ suffering, insert unknown environment (hospital), deprivation of recreational and superficial relations with healthcare professionals. already as consequences of the concept, identified the depression, manic episode, phobias, angst, suicide attempt disorder, separation anxiety disorder, generalized anxiety disorder, post-traumatic stress disorder, mood disorder, panic/ panic disorder, social anxiety disorder and obsessive compulsive disorder. Conclusions: based on the conceptual analysis of the elaborated up a proposal for a nursing diagnosis, meeting the criteria for inclusion in ICNP®, which needs to be tested in the practice of nursing as a way to connect up the knowledge to professional practice. Diagnosis Anxiety hospitalization was defined as an Anxiety with the following specific characteristics: changes in appetite, dyspnea, respiratory sensation of constriction, sympathetic stimulation - cardiovascular excitation, superficial vasoconstriction, pupil dilation, excitement, tachycardia, insomnia, increased alertness and trembling; seizure; chore; conflict; uneasiness of mind, lack of concentration, inattention, hyperactivity, impulsivity, agitation, restlessness, irritability, anger, fear, anxiety, nervousness, loss of self-confidence, insecurity, impotence, loss of autonomy; concern; sensation of abandonment, loneliness, helplessness, feeling guilt and punishment, bodily injury or assault; voltage, and sadness.